LEARNING SOCIETY: HOW DOES OLDER PEOPLE`S LEARNING CONTRIBUTE TO ITS ADVANCEMEN? - Zemaitaityte, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The article discusses the characteristics of the formation of a learning society and the learning opportunities for older adults. As international documents note, the aim of adult education and lifelong learning is to equip adults of all ages with the necessary skills to exercise and realize their rights and control their destinies. It promotes the personal and professional development of adults, the increased involvement of adults in the creation of learning communities and sustainable environments. Adult education is therefore becoming a crucial tool for reducing poverty, improving health and well-being and contributing to the creation of a sustainable learning society. Scientific literature, document analysis and secondary data analysis reveal that for construction of a learning society in Lithuania older people should be actively encouraged to join the learning process.